2021
DOI: 10.3389/fphar.2021.604811
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects and Network Analysis of Ginsenoside Rb1 Against Cerebral Ischemia Injury: A Pharmacological Review

Abstract: Ischemic stroke is a leading cause of death and disability worldwide. Currently, only a limited number of drugs are available for treating ischemic stroke. Hence, studies aiming to explore and develop other potential strategies and agents for preventing and treating ischemic stroke are urgently needed. Ginseng Rb1 (GRb1), a saponin from natural active ingredients derived from traditional Chinese medicine (TCM), exerts neuroprotective effects on the central nervous system (CNS). We conducted this review to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Thus, among the compounds with similar gene expression signatures of icariin administration, we identified another natural compound, ginsenoside Rb1. Ginsenoside Rb1, the effective ingredient of ginseng, was found to have multiple bioactive features, such as antitumor, immunoregulation, antioxidative, and neuroprotective effects ( Zhou et al, 2019 ; Ahmed et al, 2016 ; Xie et al, 2021 ). We used pharmacological network analysis and molecular docking to predict the pharmacological effect of ginsenoside Rb1, and found that it is concentrated on osteogenesis and angiogenesis and partial to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, among the compounds with similar gene expression signatures of icariin administration, we identified another natural compound, ginsenoside Rb1. Ginsenoside Rb1, the effective ingredient of ginseng, was found to have multiple bioactive features, such as antitumor, immunoregulation, antioxidative, and neuroprotective effects ( Zhou et al, 2019 ; Ahmed et al, 2016 ; Xie et al, 2021 ). We used pharmacological network analysis and molecular docking to predict the pharmacological effect of ginsenoside Rb1, and found that it is concentrated on osteogenesis and angiogenesis and partial to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…GsRb1 can also boost mitochondrial membrane potential, protect the normal oxidative stress function of mitochondria, and maintain the integrity of mitochondrial function, all of which reduce mitochondrial damage in various neurons ( Cheng et al, 2019 ). GsRb1 also inhibits the primary ROS source in vivo and lowers ROS generation by negatively regulating nicotinamide adenine dinucleotide phosphate oxidase (NOX)-1, NOX-2, and NOX-4 activity following ischemia ( Dong et al, 2017 ; Xie et al, 2021 ).…”
Section: Effect and Mechanism Of Ginsenoside Rb1mentioning
confidence: 99%
“…Recent research indicates that ginsenoside Rg1 (GRg1) prevents neurotoxicity by blocking Ca 2+ over-influx into neuronal cells to elevate intracellular Ca 2+ concentration in both MCAO/R-induced rats and OGD/R-induced neuronal cells (Zhang et al, 2013;He et al, 2014;Sun et al, 2014). Ginsenoside Rb1 (GRb1) exerts significant neuroprotective effects on CI/IR both in vivo and in vitro, and these network actions and underlying mechanisms are mediated by antioxidant, anti-inflammatory, and antiapoptotic activities and involve the inhibition of excitotoxicity and Ca 2+ influx, preservation of BBB integrity, and maintenance of energy metabolism (Xie et al, 2021). Ginsenoside F1 (GF1) promotes angiogenesis in vitro and in vivo by activating the insulin-like growth factor 1/insulin-like growth factor 1 receptor (IGF-1/IGF1R) signaling pathway (whose axis is Gastrodia elata Blume [Orchidaceae; Gastrodiae rhizome] is a famous CHM that has been traditionally used for the treatment and prevention of CI/RI for centuries (Liu et al, 2018).…”
Section: Panax Ginseng Camey(araliaceae; Ginseng Radix Et Rhizoma)mentioning
confidence: 99%